La conquête d'un espace public : les bars fréquentés par les lesbiennes - Chamberland, Line (Sortir de l'ombre : histoires des communautés lesbienne et gaie de Montréal, 1998)
Histoire bien documentée et inédite des communautés homosexuelles de Montréal. Longtemps victimes de brimades et de préjugés, les gais et lesbiennes sont finalement "sorti.e.s de l'ombre" et ont gagné de belles victoires durant les dernières décennies.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; his4860; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; montréal; premier cycle; québec; rapports sociaux de sexe; régions géographiques; sexualité; systèmes d'oppressions; thématiques; violences

Unruly women: The politics of social and sexual control in the old South - Bynum, Victoria E. (Gender & American culture, 1992)
In this richly detailed and imaginatively researched study, Victoria Bynum investigates "unruly" women in central North Carolina before and during the Civil War. Analyzing the complex and interrelated impact of gender, race, class, and region on the lives of black and white women, she shows how their diverse experiences and behavior reflected and influenced the changing social order and political economy of the state and region. Her work expands our knowledge of black and white women by studying them outside the plantation setting.Bynum searched local and state court records, public documents, and manuscript collections to locate and document the lives of these otherwise ordinary, obscure women. Some appeared in court as abused, sometimes abusive, wives, as victims and sometimes perpetrators of violent assaults, or as participants in illicit, interracial relationships. During the Civil War, women frequently were cited for theft, trespassing, or rioting, usually in an effort to gain goods made scarce by war. Some women were charged with harboring evaders or deserters of the Confederacy, an act that reflected their conviction that the Confederacy was destroying them.These politically powerless unruly women threatened to disrupt the underlying social structure of the Old South, which depended upon the services and cooperation of all women. Bynum examines the effects of women's social and sexual behavior on the dominant society and shows the ways in which power flowed between the private and public spheres. Whether wives or unmarried, enslaved or free, women were active agents of the society's ordering and dissolution.
Keywords: 1800-1899; amériques; approches et analyses; civil war; cours; discipline; féminisme matérialiste; his4443; histoire; histoire des femmes*; histoire et politique; intersectionnalité; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Pornography and civil rights: a new day for women's equality - Dworkin, Andrea; MacKinnon, Catharine A. (Organizing Against Pornography, 1988)
"Pornography is central in creating and maintaining the civil inequality of the sexes. Pornography is a systematic practice of exploitation and subordination based on sex which differentially harms women. . . ." With those bold words began the groundbreaking local antipornography law drafted by writer Andrea Dworkin and lawyer Catharine A. MacKinnon. Their completely new legal approach--in which pornography is defined as sex discrimination and therefore a violation of civil rights--would allow anyone injured by pornography to fight back by filing a civil lawsuit against pornographers. First passed in December 1983 in Minneapolis, where it was supported by a grassroots coalition of women, people of color, neighborhood groups, and the city's welfare poor and working poor, this law has transformed the way people of conscience understand the devastating impact of pornography on women's right to equality. This new law also offers hope: an effective legal tool for making sex equality real. In this comprehensive and easy-to-read guidebook, now available on line, the coauthors of the anti-pornography civil-rights ordinance explain: How pornography hurts women and how and why the civil-rights ordinance would make a difference. Why the pornography is so important to women's equality. The truth about the antipornography civil-rights ordinance--what it is, what it does, what it means, how it works. Answers to the lies about it--lies that the media have spread to protect the pornography industry. What you can do to stop the pornographers and further women's equality. "The Ordinance does not take 'rights' away from anyone, . . . it takes the power to hurt women away from pornographers." --from Pornography and Civil Rights
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; discipline; droit; droits des femmes*; féminisme anti-porn; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; science politique et droit; sex1911; sexualité; sofia; thématiques; violences; états-unis

L'Arraisonnement des femmes : essais en anthropologie des sexes - Mathieu, Nicole-Claude (Editions de l'Ecole des hautes études en sciences sociales, 1985)
Arraisonner quelqu'un, c’est en vieux français tenter de le persuader, argumenter pour lui faire entendre raison. En termes de marine et de police sanitaire, arraisonner un navire, c'est l'interpeller, interrompre sa route pour le contrôler. Ainsi, c'est de la double face, matérielle et mentale, du contrôle et de la manipulation des femmes que traite ce livre collectif. Par l'analyse de sociétés très diverses, anciennes et modernes, comme par la critique des discours scientifiques, les auteurs — ethnologues, sociologues, linguistes – éclairent avec rigueur et imagination théoriques deux domaines encore peu explorés de la problématique des sexes : 1) L’élaboration sociale (politique) de la sexualité et la manipulation des mécanismes de la reproduction — dont l'exposé dément les explications naturalistes ; 2) Les conditions socio-sexuées de la connaissance, les effets sur la conscience de l’oppression matérielle subie et exercée — dont l'analyse exclut toute explication idéaliste. Si les deux sexes sont socialement construits, ce n'est pas de façon symétrique. Objets de raisonnements réducteurs et réduites dans leur corps et dans leur raison, soumises à persuasion ou raisonnées de force, inspectées, contrôlées dans leur tête et dans leur ventre tel un navire sa cargaison, son état sanitaire, son port d'attache : ainsi sont-elles créées « femmes » dans de multiples sociétés. Ainsi s'exerce l'arraisonnement des femmes.
Keywords: 1900-1999; anthropologie; approches et analyses; cours; discipline; domination masculine; europe; fem1000; france; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; violences; violences contre les femmes*

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences

Pleasure and danger: Exploring female sexuality - Vance, Carole S. (Routledge & Kegan Paul, 1984)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality - Vance, Carole S. (Pleasure and danger: exploring female sexuality, 1984)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; plaisir féminin; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sex1183; sexualité; sexualité des femmes*; thématiques; violences; états-unis

Pratique du pouvoir et idée de Nature (1) : l’appropriation des femmes - Guillaumin, Colette (Nouvelles Questions Féministes, 1978)
Dans les rapports de genre, le fait que les hommes puissent s'assurer la force de travail des femmes sans contrepartie mesurable (en temps, en argent, etc.) montre que la nature de la relation est différente de celle de la vente classique du travail. Comme dans l'esclavage et le servage, il y a appropriation directe de la base matérielle – corporelle – de l'individu. Cette appropriation se manifeste, dans la forme matrimoniale de cette relation, par le fait que le travail n'est pas évalué, par l'appropriation des produits – parmi lesquels les enfants –, par le droit illimité d'utiliser le corps de l'épouse. Elle s'exprime par la nature de certaines tâches : la responsabilité, par exemple, des besoins corporels du dominant et de ses dépendants. Ces tâches sont empiriquement associées à l'appropriation corporelle (du dominé), par exemple dans l'esclavage. La relation sociale que l'on pourrait appeler « sexage » est à la fois collective (appropriation collective des femmes par les hommes) et privée (comme dans le mariage, qu'il soit légal ou de droit commun).
Keywords: approches et analyses; care; discipline; domination masculine; féminisme matérialiste; patriarcat; rapports sociaux de sexe; ressource en ligne; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; violences

Violence et contrôle social des femmes - Hanmer, Jalna (Questions Féministes, 1977)
Keywords: 1900-1999; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences